Digital Marketing Communication Strategy for Local Perfume Brand HMNS @hmns.id - Putri, Rr. Tasya Amalia; Nurhaqiqi, Hanna (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Abstract:This research discusses the digital marketing communication strategy implemented by local perfume brand HMNS via the social media platform Instagram. The aim of this research is to determine the digital marketing communication strategy carried out by the local perfume brand HMNS. This research method uses qualitative descriptive research with data collection techniques carried out using observation, in-depth interviews, documentation and literature study. The results of this research show that the HMNS perfume brand uses various digital marketing strategies, including the use of Instagram as the main marketing media, the application of the Integrated Marketing Communication (IMC) concept with a focus on building relationships with customers, story telling strategies, the use of advertising, sales promotion and public relations. which is supported by the marketing mix concept.